2006
DOI: 10.1021/jp062222a
|View full text |Cite
|
Sign up to set email alerts
|

Disintegration Mechanisms of Charged Aqueous Nanodroplets Studied by Simulations and Analytical Models

Abstract: The mechanism of fragmentation processes in aqueous nanodroplets charged with ions is studied by molecular dynamics (MD) simulations. By using constant-temperature MD, the evaporation of the water is naturally taken into account and sequences of ion fragmentation events are observed. The size of the critical radius of the charged droplet just before the fragmentation and the distribution of the sizes of the fragments are estimated. Comparison of the Rayleigh critical radius for fragmentation and simulation dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
64
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(67 citation statements)
references
References 45 publications
3
64
0
Order By: Relevance
“…Distinct from these experimental and theoretical efforts, a number of researchers, beginning with Znamenskiy et al 20 and including the works of Consta and colleagues [21][22][23] as well as Konermann and colleagues [24][25][26] , have used Molecular Dynamic (MD) simulations to directly observed, computationally, ions evaporating from nanodrops. Notable amongst these prior works, Ichiki & Consta 23 computed the approximate radii of evaporating, solvated chloride ions from water drops in simulations, finding good agreement with model predictions of Labowsky et al 17 .…”
Section: Introductionmentioning
confidence: 99%
“…Distinct from these experimental and theoretical efforts, a number of researchers, beginning with Znamenskiy et al 20 and including the works of Consta and colleagues [21][22][23] as well as Konermann and colleagues [24][25][26] , have used Molecular Dynamic (MD) simulations to directly observed, computationally, ions evaporating from nanodrops. Notable amongst these prior works, Ichiki & Consta 23 computed the approximate radii of evaporating, solvated chloride ions from water drops in simulations, finding good agreement with model predictions of Labowsky et al 17 .…”
Section: Introductionmentioning
confidence: 99%
“…For deriving eq 1, Rayleigh [32] assumed that fragmentation is triggered by shape oscillations. Droplet deformations were described in terms of spherical harmonics, and he concluded that the fragmentation channel having the lowest ⌬E ts is associated with quadrupole (prolate-oblate [9]) oscillations, whereas higher order deformations are less effective at mediating disintegration [42]. For a neutral droplet (f ( ( ϭ 0) disintegration is highly endothermic due to the increase in total surface area.…”
Section: Introductionmentioning
confidence: 99%
“…E lectrospray ionization (ESI) mass spectrometry (MS) has evolved into one of the most versatile and widely used analytical techniques. The ESI process itself has been subject of numerous studies (see, e.g., [1][2][3][4][5][6][7][8][9][10][11][12] and references therein). Analyte solution is passed through a metal capillary to which high voltage has been applied, and solvent droplets emanate from the tip of a Taylor cone at the capillary outlet [11].…”
mentioning
confidence: 99%
See 2 more Smart Citations